Functional role of AhR in the expression of toxic effects by TCDD - Mimura, Junsei; Fujii-Kuriyama, Yoshiaki (BBA - General Subjects, 2003)
Cytochrome P450 1A1 ( CYP1A1) is one of the xenobiotic metabolizing enzymes (XMEs), which is induced by polycyclic aromatic hydrocarbons (PAHs). The most potent inducer of CYP1A1 is 2,3,7,8-tetrachlorodibenzo- p-dioxin (TCDD). In addition, TCDD induces a broad spectrum of biochemical and toxic effects, such as teratogenesis, immunosuppression and tumor promotion. Most, if not all, of the effects caused by TCDD and other PAHs are known to be mediated by AhR (aryl hydrocarbon receptor or dioxin receptor) which has a high binding affinity to TCDD. The liganded AhR translocates from cytoplasm to nuclei where it switches its partner molecule from Hsp90 to Arnt. Thus formed AhR/Arnt heterodimer binds a specific DNA sequence designated XRE in the promoter region of the target genes including CYP1A1, UDP- glucuronosyl transferase and others to enhance their expression. Although it remains to be studied how AhR is involved in the other TCDD-induced biological effects such as teratogenesis and immunosuppression than induction of XMEs, it is believed that these adverse TCDD effects are caused by untimely activation of gene expression by ligand-activated AhR in the biological process. We summarize the present knowledge about functional role of AhR in TCDD-induced biological effects.